Profil Kondisi Fisik Mahasiswa Pendidikan Jasmani Universitas Samudra - Julio Roberto; Fitria (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Physical condition is the ability to function the body's organs in carrying out physical activities. Good physical condition is really needed by students in carrying out the lecture process, especially in carrying out practical courses. This research aims to determine the physical condition of Physical Education Study Program students for the active semester. This research is descriptive research. The subjects of this research were students of the Active Semester Physical Education Study Program at Samudra University. Data collection uses tests and measurements. The instruments used in this research have been tested for validity and reliability. The instruments used were body composition measurements using the Omron Body Fat Monitor, speed tests using the 60 meter sprint test, agility tests using the Illinois Agility Run Test, coordination tests using throwing and catching a tennis ball, balance tests using the Strock Standing Balance Test, flexibility tests using the Sit. and reach test, endurance test with multistage fitness test. The data analysis technique uses quantitative descriptive analysis in the form of percentages.